Energy saving potential of cement-based mortar containing hybrid phase change materials applied in building envelopes - Kheradmand, Mohammad (2016)
This work reports an experimental study regarding the energy saving potential of an innovative concept of thermal energy storage, which consists in embedding more than one type of Phase Change Material (PCM) into cement-based mortars to apply as renderings in façade walls of buildings. The mortar simultaneously incorporates three distinct phase change materials and is termed HPCMM (Hybrid PCM mortar). The total mass percentage of PCMs in HPCMM can reach as high as 20%, while maintaining satisfactory performance in terms of mechanical properties/behavior of the mortar. The experimental program comprises two laboratory scale prototypes,materialized by two hollow boxes of outer dimensions 46×46×46cm 3, internally coated with HPCMM or REFM (reference mortar without PCM) and externally subjected to realistic daily temperature profiles. The prototypes were internally equipped with a heater that was programmed to keep the inside of the box within the acceptable range of comfort temperature, in correspondence to the simulation of a winter scenario (heating season). By monitoring the energy consumption of the heater, it was possible to infer that the prototype rendered with HPCMM led to a reduction of energy consumption of nearly 20% as compared to the prototype rendered with REFM.